Shrub and precipitation interactions shape functional diversity of nematode communities on the Qinghai–Tibet Plateau. Issue 10 (1st March 2023) - Zhang, Anning; Chen, Shuyan; Chen, Jingwei; Cui, Hanwen; Jiang, Xiaoxuan; Xiao, Sa; Wang, Jiajia; Gao, Haining; An, Lizhe; Cardoso, Pedro
Abstract: Land use and climate change alter biodiversity patterns and ecosystem functioning worldwide. Land abandonment with consequent shrub encroachment and changes in precipitation gradients are known factors in global change. Yet, the consequences of interactions between these factors on the functional diversity of belowground communities remain insufficiently explored. Here, we investigated the dominant shrub effects on the functional diversity of soil nematode communities along a precipitation gradient on the Qinghai–Tibet Plateau. We collected three functional traits (life‐history C – P value, body mass, and diet) and calculated the functional alpha and beta diversity of nematode communities using kernel density n ‐dimensional hypervolumes. We found that shrubs did not significantly alter the functional richness and dispersion, but significantly decreased the functional beta diversity of nematode communities in a pattern of functional homogenization. Shrubs benefited nematodes with longer life‐history, larger body mass, and higher trophic levels. Moreover, the shrub effects on the functional diversity of nematodes depended strongly on precipitation. Increasing precipitation reversed the effects shrubs have on the functional richness and dispersion from negative to positive but amplified the negative effects shrubs have on functional beta diversity of nematodes. Benefactor shrubs had stronger effects on the functional alpha and beta diversity of nematodes than allelopathic shrubs along a precipitation gradient. A piecewise structural equation model showed that shrubs and its interactions with precipitation indirectly increased the functional richness and dispersion through plant biomass and soil total nitrogen, whereas it directly decreased the functional beta diversity. Our study reveals the expected changes in soil nematode functional diversity following shrub encroachment and precipitation, advancing our understanding of global climate change on nematode communities on the Qinghai–Tibet Plateau. Abstract : Shrubs did not significantly alter the functional richness and dispersion, but significantly decreased the functional beta diversity of nematode communities in a pattern of functional homogenization. Shrubs benefited nematodes with longer life‐history, larger body mass, and higher trophic levels. Increasing precipitation reversed the effects shrubs have on the functional richness and dispersion from negative to positive but amplified the negative effects shrubs have on functional beta diversity of nematodes.